(3GdUGgd hGdTGMLs - (3CMeO Hf YHO Gddg Hf SdjeGf GdJfhNj , CHh GdYdGA GdeYQj , J (B449 (3g` s
(3ChdgG (B:s
(3bGd CHhGdYdGA CSde Ydi GdMVQI GdYGdjI, JSdje GdYGLR GdebUQ s
(3BNQgG (B:s
(3hEfeG YfjJ bhd GdhdjO(B: (3hdc GdSdGeI hGdSdGe aEffj eGmV hgf Ydi YdGc MHGFS cedJ QSGdI GdUGgd hGdTGML hGdMeO ddg s
(3GdfSNI HgG MhGTs
(3Yf fSNI cJHJ aj SHJI aj TgQ TYHGf SfI (B693(3g`s
(3fSNI KGfjIs
(3JJab aj ChdgG hBNQgG eY GdfSNI GdChdi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B157 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B290s
Keywords: (3GdCOHs